2013
DOI: 10.1177/0009922813506606
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Crying Facies in the 22q11.2 Deletion Syndrome

Abstract: We report a 14% incidence of ACF in patients with a 22q11.2 deletion, significantly higher than in the general population. We suggest, therefore, that newborns with ACF be referred for further screening for the 22q11.2 deletion syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 32 publications
0
21
0
1
Order By: Relevance
“…These features are variable and less frequently identified in non-Caucasians (McDonald-McGinn et al, 2015). Reduced facial affect (Gerdes et al, 1999) and/or animation are often seen as well as asymmetric crying facies (Pasick et al, 2013). For photographic examples of dysmorphic facial features in 22qDS across age and ethnicity, see McDonald-McGinn et al, 2015.…”
Section: Overview Of 22qdsmentioning
confidence: 99%
“…These features are variable and less frequently identified in non-Caucasians (McDonald-McGinn et al, 2015). Reduced facial affect (Gerdes et al, 1999) and/or animation are often seen as well as asymmetric crying facies (Pasick et al, 2013). For photographic examples of dysmorphic facial features in 22qDS across age and ethnicity, see McDonald-McGinn et al, 2015.…”
Section: Overview Of 22qdsmentioning
confidence: 99%
“…Movement abnormalities are common in children and adolescents with 22q11.2DS. These include hypotonia in infancy, delayed gross‐motor milestones [Swillen et al, ], specific motor deficits in axial stability [Roizen et al, ], deficits in psychomotor speed [Howley et al, ], problems with coordination and balance [van Aken et al, ], asymmetric crying face [Pasick et al, ], seizures, and tremor or tetany as a result of hypocalcemia [Weinzimer, ].…”
Section: Introductionmentioning
confidence: 99%
“…5 In a retrospective review, a 14% incidence of ACF was reported in patients with 22q11DS, significantly higher than the incidence in the general population (0.6%). 6 The presence of concurrent cardiovascular anomalies and palatal/ velopharyngeal abnormalities among patients with both the 22q11.2DS, and ACF did not differ significantly from that in the population of all patients with 22q11.2DS. No pathogenic CNVs were detected using array-CGH in our patient.…”
Section: Discussionmentioning
confidence: 77%